BMP2/7 heterodimer enhances osteogenic differentiation of rat BMSCs via ERK signaling compared with respective homodimers. Issue 5 (28th November 2018) - Miao, Chunlei; Qin, Dengke; Cao, Peigang; Lu, Ping; Xia, Yutong; Li, Mengjiao; Sun, Miao; Zhang, Wei; Yang, Fanghong; Zhang, Yingjie; Tang, Shengjian; Liu, Tianyi; et al.
Abstract: Bone morphogenetic protein (BMP)2/7 heterodimer shows greater efficacy in enhancing bone regeneration. However, the precise mechanism and the role of mitogen‐activated protein kinase (MAPK) signaling network in BMP2/7‐driven osteogenesis remain ambiguous. In this study, we evaluated the effects of BMP2/7 heterodimers on osteoblastic differentiation in rat bone marrow mesenchymal stem cells (BMSCs), with the aim to elaborate how MAPKs might be involved in this cellular process by treatment of rat BMSCs with BMP2/‐7 with a special signal‐pathway inhibitor. We found that BMP2/7 heterodimer induced a much stronger osteogenic response in rat BMSCs compared with either homodimer. Most interestingly, extracellular signal‐regulated kinase (ERK) demonstrated a highly sustained phosphorylation and activation in the BMP2/7 heterodimer treatment groups, and inhibition of ERK cascades using U0126 special inhibitor that significantly reduced the activity of ALP and calcium mineralization to a substantial degree in rat BMSCs treated with BMP2/7 heterodimers. Collectively, we demonstrate that BMP2/7 heterodimer shows a potent ability to stimulate osteogenesis in rat BMSCs. The activated ERK signaling pathway involved in this process may contribute partially to an increased osteogenic potency of heterodimeric BMP2/7 growth factors. Abstract : The precise mechanism and the role of mitogen‐activated protein kinase (MAPK) signaling in bone morphogenetic protein (BMP)2/7 heterodimer–enhanced bone regeneration remain unknown. Data showed that BMP2/7 heterodimer induced much stronger osteogenic response in rat bone marrow mesenchymal stem cells (BMSCs), and the activated extracellular signal‐regulated kinase (ERK) signaling involved in this process may contribute to the enhanced osteogenic potency of heterodimeric BMP2/7 growth factors.